Pengaruh Pembelajaran Organisasi, Kepemimpinan, Lingkungan Kerja Terhadap Motivasi Pegawai Kecamatan Karimun Untuk Peningkatan Disiplin Kerja Pegawai - Haryono .; Raden Richky Dwi Muhardin; Permana Tedjo . (Jurnal Manajemen Maranatha, 2011)
This research want to understand the influence of learning organization, leadership, a work environment against motivation clerk subdistricts karimun for an increase discipline of work employees. This research uses the approach of quantitative. The data used is data a primer that obtained from 65 of the respondents. The technique of the analysis that used is the path of analysis. There are the influence of being significant and markedly between variables of learning organization (X1), leadership (X2) and a work environment (X3) impact on motivation (Y1), Twhere obtained that the value of Tstatistic on each of exogen variable > Ttable of 1.99897. There are the influence of being significant and markedly between variables of learning organization (X1), leadership (X2), a work environment (X3) and motivation (Y1) have an effect upon discipline of work (Y2), where obtained that the value of Tstatistic on each of exogenous variable > Ttable of 1.99897. There are influences of being significant and markedly between variables exogenous with a variable endogenous, where the magnitude of the influence of obtained amounting to, 6629 or 66.29%. It is notice the magnitude of the influence of a whole exogenous variable against a variable endogenous amounting to 67.97% and the rest amounting to 32.13% caused by other variables.Keywords: Learning Organization, Leadership, A Work Environment, Motivation Work, Employees Work Employees Discipline